Efficacy of a synthetic zeolite against five species of stored-grain insects on concrete and wheat - Yao, Kouame (Kansas State University, 2014)
A synthetic zeolite (Odor-Z-Way, sodium aluminum silicate) used for odor adsorption was tested for its ability to control adults of stored-grain insects on wheat and on concrete petri dishes used to simulate floors of empty bins. Insect species tested included unsexed adults of the lesser grain borer, Rhyzopertha dominica (F.); rice weevil, Sitophilus oryzae (L.); maize weevil, Sitophilus zeamais (Motschuslky); red flour beetle, Tribolium castaneum (Herbst), and sawtoothed grain beetle, Oryzaephilus surinamensis (L.). Two formulations were evaluated under laboratory conditions (28±1⁰C and 65±1% r.h.): coarse zeolite (with 90% of particles having a mean diameter at or below 155 µm) and fine zeolite (with 90% of particles having a mean diameter at or below 47.0 µm). On concrete, arenas in 9-cm diameter Petri dishes were sprinkled with the synthetic zeolite to provide deposits of 0 (control), 5 and 10 g/m[superscript]2. Mortality was assessed at times ranging from 10 minutes to 24 hours followed by 48 hours recovery on wheat. Mortality in adults of the five species increased as the rate of application and the duration of exposure increased. Concrete Petri dishes sprinkled with the fine zeolite yielded percent mortality greater or equal to that observed with the coarse zeolite- sprinkled Petri dishes. Bioassays on wheat were conducted using two dosage rates: 0.1 to 3.0 g/kg for R. dominica and 0.05 to 1.0 g/kg for the other insect species. Mortality was assessed 7 days post- infestation. A concentration of 0.75 g/kg of fine or coarse zeolite achieved 100% mortality in adults of S. zeamais, T. castaneum, and O. surinamensis. All adults of S. oryzae were killed using 0.50 g/kg of coarse or fine zeolite. Adults of R. dominica were the least susceptible: 2.50 g/kg of fine zeolite and 3.0 g/kg of coarse zeolite were required for 100% mortality. Mortality generally increased with the concentration of zeolite applied on wheat. Efficacy was not related to particle size. This is the first study showing the efficacy of a synthetic zeolite against adults of five species of stored-product insects on concrete and wheat. Synthetic zeolites can be a suitable alternative to currently used pesticides for treatment of empty bin floors and stored wheat for insect control.
Keywords: Stored-grain insects; Synthetic zeolite; Concrete surfaces; Wheat; Pest management; Efficacy assessment; Agriculture, General (0473)